Geological prerequisites for the search for rocks with increased reservoir properties in domanic type sediments on the territory of the Republic of Tatarstan - V. P. Morozov; A. S. Khayuzkin; E. A. Korolev; A. N. Kolchugin; A. N. Mukhamediyarova; E. V. Morozova; A. A. Eskin; N. A. Nazimov; F. M. Gazeeva; N. S. Zakharova (Georesursy, 2024)
Domanic type deposits generally is abundant in Tatarstan Republic and other territories. They are feature with oil-source rocks (black shales), which partly generated hydrocarbons. However, due to their high hydrocarbon contain, domanic type deposits construing as unconventional reservoir rocks, that may be commercial significant. Based on Russian and foreign experience in the development of such deposits, the prospects for their exploitation are associated with the searching for formations with increased reservoir properties and light oil.In this work we are analyzed the stratigraphic distribution of domanic type deposits in the Kama-Kinel system of depressions and beyond them. It is shown that such deposits in the Kama-Kinel system of depressions have a thickness about 300 m and cover the stratigraphic range from semiluk horizon of the Frasnian stage to Tournaisian stage. But out of depressions these rocks occurred only in semiluk horizon. The reason of it is high dissection of the bottom of the Domanic sedimentation basin in the Late Frasnian-Tournaisian ages due to the evolution of the Kama-Kinel system of depressions in the east of the Russian Plate.The results of our own research show that carbonate and carbonate-siliceous rocks enriched in organic matter are the most common lithotypes in the Domanic type deposits. Also, we constantly found carbonate breccias and less secondary dolomites in the studied geological columns. In the last two types of rocks, we found higher values of porosity, openness, and a lighter composition of hydrocarbons. Based on the results of the author’s research and the literature observation, it follows that the development of carbonate breccias and secondary dolomites will be in the sides of the Kama-Kinel system of depressions. We consider that they are as the most promising objects for the search for industrial profit in the Domanic type deposits.